GENDER DIFFERENCES, TREND AND PATTERN RECIDIVISM AMONG INMATES IN SELECTED NIGERIAN PRISONS - Abrifor, C. A.; Atere, A. A.; Muoghalu, C. O. (European Scientific Journal, ESJ, 2012)
The study examined gender perception and the prevalence of recidivism in Nigerian prisons; it ascertained the trend and pattern of crimes by recidivists. This was with a view to establishing the gender differences, their patterns of crime, relationships and behavioural predispositions. Primary and secondary data were generated; the primary data were collected in five purposively selected State Prison Commands. The quantitative data was collected. Quantitative data were collected through questionnaire; a sample of 567 inmates was selected using proportional sampling technique. The quantitative data collected were analysed using descriptive and inferential statistics. The results showed persistent rise in the prevalence of recidivism from 35% in 2007 to 44% in 2008 and 52.4% in 2010. The trend and pattern of recidivism showed that male recidivists constituted 88.5% while females, 11.5% and the prevalence was high among young offenders and within the age groups of 26-35 years (54.0%), 36 -45years (22.2%) and 16 -25 years (21.2%). The trend and patterns of crimes were mostly theft and other minor stealing (20.3%), armed robbery (11.3%) and burglary (9.0%). Female recidivists were convicted for anger related offences such as murder (10.1%) and attempted murder cases (6.2%). The study concluded that there was a constant increase in the prevalence of recidivism; especially among male inmates and that most crimes¸ patterns of relationships and behavioural predispositions were offender specific.